Penguatan Manajemen Rantai Pasok Pakan Ayam Petelur melalui Budidaya Maggot Black Soldier Fly Berbasis Limbah Organik - Ilham Assidiq; Muhammad Bibin; Rista Astari Rusdin; Muh Achyar Ardat; Suharman (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to strengthen feed supply chain management among laying hen farmers through the cultivation of Black Soldier Fly (BSF) larvae using organic waste as an alternative protein source. The program was implemented in Batu Mila Village, Enrekang Regency, involving 25 members of the Harapan Jaya Farmers Group. A participatory approach was employed through four stages: socialization, training, technology implementation, and mentoring. Program outcomes were evaluated using pre-test and post-test questionnaires, and the data were analyzed descriptively. The results showed improved participants' knowledge and skills in BSF cultivation, organic waste management, feed formulation, and farm business management. The established BSF production unit produced an average of 7.5 kg of fresh larvae, equivalent to approximately 1.5 kg of maggot meal per day, by utilizing 35–40 kg of organic waste daily. The program also strengthened the institutional capacity of the farmers' group through the development of standard operating procedures (SOPs), production recording systems, and simple bookkeeping practices. Overall, the program enhanced farmers' capacity to utilize local resources, reduced dependence on commercial feed, and promoted the adoption of a more sustainable, circular economy-based feed supply system.